Wielowymiarowość postaw wobec integracji społecznej osób z niepełnosprawnością - Kazanowski, Zdzisław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Artykuł prezentuje propozycję narzędzia do badania akceptacji społecznej osób z niepełnosprawnością. Umieszczono w nim zarówno teoretyczne podstawy konstrukcji kwestionariusza, jak i jego właściwości psychometryczne. Biorąc pod uwagę uzyskane wyniki, można go uznać za wartościowe narzędzie diagnozowania różnic międzygrupowych oraz efektów programów wychowawczych w zakresie akceptacji osób z niepełnosprawnością.

The article presents a proposal for a tool for studying the social acceptance of people with disabilities. It contains both the theoretical basis on which the questionnaire was constructed as well as its psychometric properties. Taking into consideration the results obtained, it can be recognised as a valuable tool for diagnosing the effects of educational programs and intergroup differences in the acceptance of people with disabilities.
Multidimensionality of Attitudes Towards the Social Integration of People with Disabilities
Keywords: akceptacja osób z niepełnosprawnością; konstruowanie skal pomiarowych; postawa; acceptance of people with disabilities; construction of measuring scales; attitude